The Effect of Thermal Care Workshop on EMS Staff Readiness in Managing Accidental Hypothermia in Trauma Patients - Pourrrezaei S; Dinmohammadi MR; Jafari Rohi A (Zanjan University of Medical Sciences and Health Services, 2018)
Background: Hypothermia is a common complication in trauma patients. Studies show that the management of hypothermia in trauma patients in the pre-hospital phase may be underestimated. Objectives: The purpose of this study was to evaluate the effect of thermal care workshop on the staff readiness to manage hypothermia in trauma patients. Methods: This quasi-experimental study utilized convenience sampling after obtaining the approval of the Research Ethics Committee and involved 60 qualified EMS staff who were divided into two groups including: intervention group (30 technicians) and control group (30 technicians). The intervention group received the treatment in the form of a workshop. Nonetheless, the control group did not receive any educational intervention. The data were collected before, immediately after and 45 days after the workshop to determine EMS staff readiness using a validated researcher-made questionnaire. In this study, the significance level was 0.5. Results: There was a significant difference between the posttest results of the control group and the intervention group (p<0.001). Moreover, in the intervention group, there were significant differences between the pretest results and the two posttest results (p<0.001). Finally, the readiness gained after the workshop lasted for 45 days. Conclusion: The thermal care workshop enhanced the readiness of emergency medical personnel. The generalization of the results of this study is restricted due to the fact that random selection and random assignment of participants were not possible in the present study. It is recommended that more robust studies be designed to evaluate, prevent and manage hypothermia in trauma patients in the pre-hospital phase